An Assessment of the Cyto-Genotoxicity Effects of Green-Synthesized Silver Nanoparticles and ATCBRA Insecticide on the Root System of Vicia faba - May A. Al-Saleh; Hanan F. Al-Harbi; L. A. Al-Humaid; Manal A. Awad (Nanomaterials)
We aimed to synthesize silver nanoparticles (AgNPs) using Elettaria cardamomum (cardamom) extracts and assess the cytotoxicity and genotoxicity of the cardamom extract, cardamom–AgNPs, and the insecticide ATCBRA—commonly used for pest control—on the root system of Vicia faba (broad bean). The chemical composition of the aqueous cardamom extract was identified and quantified using GC-MS, revealing a variety of bioactive compounds also present in cardamom essential oil. These included α-terpinyl acetate (21.3–44.3%), 1,8-cineole (10.7–28.4%), and linalool (6.4–8.6%). The successful green synthesis of AgNPs was confirmed through various micro-spectroscopic techniques, including UV-Vis spectroscopy, transmission electron microscopy (TEM), and energy-dispersive spectroscopy (EDS). UV-Vis analysis showed a strong peak between 420 and 430 nm, indicating the presence of AgNPs. TEM imaging revealed that the synthesized cardamom–AgNPs were monodispersed, primarily spherical, and semi-uniform in shape, with minimal aggregation. EDS analysis further confirmed the composition of the nanoparticles, with cardamom–AgNPs comprising around 60.5% by weight. Cytotoxicity was evaluated by measuring the mitotic index (MI), and genotoxicity was assessed by observing chromosomal aberrations (CAs). The roots of Vicia faba were treated for 24 and 48 h with varying concentrations of ATCBRA pesticide (0.1%, 0.3%, 0.5%, and 0.7%), aqueous cardamom extract (3%, 4%, 5%, and 6%), and green-synthesized cardamom–AgNPs (12, 25, and 60 mg). The cytogenetic analysis of MI and CA in the meristematic root tips indicated an improvement in the evaluated parameters with the cardamom extract. However, a marked reduction in mitotic activity was observed with both ATCBRA and cardamom–AgNP treatments across both time points, highlighting potential cytotoxic and genotoxic effects.